A Effects of Psychological Empowerment on the Quality of Job Performance: The Mediating Role of Affective Organizational Commitment - Banin, Qori Al (Universitas Dr. Soetomo, 2024)
This research aims to determine and analyze the influence of each variable on performance quality at health sciences universities in Central Java, where performance quality is a very crucial component in maintaining and improving organizational sustainability. This research method uses a quantitative method, the sampling technique uses a random sampling technique, using an instrument in the form of a questionnaire which is distributed to respondents via Google Form. The number of respondents was 210 people but 126 respondents met the criteria. Random sampling is a sampling technique. The analysis technique uses SEM SmartPLS to test existing hypotheses. The results of this research show that affective organizational commitment has an influence on the quality of work performance. The three independent variables in this case competence, meaning, self-determination and impact can also influence the organization's affective commitment. It can also be said that affective organizational commitment in increasing the sustainability role of health sciences universities is very important. The theoretical implications of this research are expected to develop existing theories used in this research and have practical implications to contribute to decision makers in health science universities.